Income support, (un-)employment and well-being - Clemens Hetschko; Ronnie Schöb; Tobias Wolf (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2016)
Using specific panel data of German welfare benefit recipients, we investigate the non-pecuniary life satisfaction effects of in-work benefits. Our empirical strategy combines difference-in-difference designs with synthetic control groups to analyze transitions of workers between unemployment, regular employment and employment accompanied by welfare receipt. Working makes people generally better off than being unemployed, but employed welfare recipients do not reach the life satisfaction level of regular employees. This implies that welfare receipt entails non-compliance with the norm to make ones own living. Our findings allow us to draw cautious conclusions on employment subsidies paid as welfare benefits.
Keywords: I31; I38; J60; J68; 330; life satisfaction; subsidized employment; unemployment; income support; in-work benefits; social norms